KAPASITAS DAN STRATEGI KELEMBAGAAN PEMERINTAH DALAM PENGELOLAAN KONFLIK ANTAR PENGGUNA SUMBERDAYA PERAIRAN KABUPATEN TANAH LAUT (Capacity and Strategy of Government’s Institution on Conflict Management Between Territorial Resource Waters User) - . Rusmilyansari; Erwin Rosadi; . Apriansyah (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2014)
ABSTRACTEnactment of Law No. 32 of 2004 on Regional Government, to provide flexibility in managing resources territorial waters. The biggest challenge in the district of South Kalimantan is a conflict between water users. This study aimed to: determine the status of government agencies and determine the government priorities in conflict management of territorial waters users. The study was conducted in South Kalimantan. The method used in this study is the Institutional Development Framework. Data retrieval techniques with purposive sampling of government institutions that play a role in conflict management. The results showed that the institutional capacity of government approaching stabilization stage, while the Navy and DitPolair are already at the stage of stabilization. Priorities of government agencies in managing conflict consists of monitoring and evaluation, communication and coordination, staff appreciation, control systems, tasks and authority. Strategies institutional security apparatus consists of participation in decisions, planning participation and conflict management training.Key words: capacity, conflict, goverment, institutional, strategy-------ABSTRAKDiberlakukannya Undang-Undang No. 32 Tahun 2004 tentang Pemerintah Daerah, memberikan keleluasaan dalam melakukan pengelolaan sumberdaya perairan teritorial. Tantangan terbesar di Kabupaten Tanah Laut Kalimantan Selatan adalah konflik antar pengguna perairan. Penelitian ini bertujuan untuk: mengetahui status kelembagaan pemerintah dan mengetahui prioritas kerja kelembagaan pemerintah dalam pengelolaan konflik pengguna perairan teritorial. Penelitian dilakukan di Kalimantan Selatan. Metode penelitian menggunakan Institutional Development Framework. Teknik pengambilan data dengan purposive sampling terhadap institusi pemerintah yang berperan dalam pengelolaan konflik. Hasil penelitian menunjukkan bahwa kapasitas kelembagaan pemerintah mendekati tahap pemantapan, sedangkan TNI AL dan DitPolair sudah berada pada tahap pemantapan. Prioritas kerja kelembagaan pemerintah dalam melakukan pengelolaan konflik terdiri dari komponen monitoring dan evaluasi, komunikasi dan koordinasi, penghargaan staf, sistem pengendalian, tugas dan kewenangan. Strategi kelembagaan aparat keamanan terdiri dari partisipasi dalam keputusan, partisipasi perencanaan dan pelatihan pengelolaan konflik.Kata kunci: kapasitas, konflik, pemerintah, kelembagaan, strategi